Application of LQ-moment ratio diagram in selecting the best distribution - Ani bin Shabri; Abdul Aziz Jemain (Universiti Kebangsaan Malaysia, 2010)
The method of moments has been one of the simplest and conventional parameter estimation techniques used in statistical hydrology. However, moment estimates are usually inferior in quality and generally not as efficient as the L-moment estimates, especially for distribution with three or more parameters. Of late, many regional frequency studies in hydrology use the L-moment ratio diagram to select the most appropriate distribution of hydrologic and meteorological data. An advantage of L-moment ratio diagrams is that one can compare the fit of several distributions using a single graphical instrument. The purpose of this paper is to revisit the LQ moments and to develop the LQ-moments ratio diagrams based on median estimator. Using flood-flow data at 73 stations in Peninsular Malaysia, we explored the suitability of various flood frequency models using LQ-moments ratio diagrams compared with L-moments ratio diagrams. The result shows that the new diagrams perform as well as L-moments ratio diagrams for selecting a suitable frequency distributions and makes it an attractive option in flood frequency analysis.